Retail chain affiliation and time trend effects on inventory turnover in Norwegian SMEs - Jørgen Breivik (Cogent Business & Management, 2019)
Inventory is a significant and important asset for retailers and represents what a store has to offer its customers for instant purchase; at the same time, considerable costs are associated with holding inventory. In this study, we use inventory turnover as a measure of inventory performance. We build upon previous research and use firm-specific measures to untangle the link between inventory performance and chain affiliation as well as time trends for SMEs. We employ panel regressions on data for the 1998-2013 period for Norwegian stores affiliated with three different retail chains that operate within the industry of retail sale of hardware, paints and glass. We estimate inventory turnover both with and without controlling for explanatory variables, and we find that inventory performance over the sampling period varies but decreases over time for the examined retail chains controlling for factors known to affect relative inventory levels. We further find that retail chain affiliation affects inventory turnover at the store level when controlled for gross margin, capital intensity, growth in sales, and that inventory increases with firm size. These findings have important implications for practice.
Keywords: 650; inventory turnover; inventory leanness; inventory management; inventory performance